Letter - Adler, Friedrich, 1879-1960
021-0048-001 Mr Tewson - to speak to Mr Gillies 9039 INTERNATIONALE OUVRIERE SOCIALISTE LABOUR AND SOCIALIST INTERNATIONAL BRUXELLES, March 5th, 1937. SOZIALISTISCHE ARBEITER-INTERNATIONALE Secrétariat: BRUXELLES, 162, rue de Laeken Adresse telegraphique - Telegrams - Telegrammaresse: INTERSOCIA BRUXELLES Téléphones: 17,70,36 et 17,70,37 P/L. EXPRESS Mr. William Gillies, International Secretary, The Labour Party, Transport House, Smith Square, London, S.W.1. My dear Gillies, We assume that the arrangements for the office work in connection with our meetings next week can be made when we arrive in London. There is only one point in connection with which a difficulty might arise, namely the question of typewriters. There is no need for us to ask for machines with Continental keyboards, but it would be a great help to us if we could have one or two machines with French and German accents. While we are meeting at Transport House we assume that it will be possible for us to have a room for our office work and to obtain the necessary paper, and so on. The same room would do for the I.F.T.U. people as well. When we remove to Central Hall for the Conference it will be necessary for us to have a room there too. Perhaps this was thought of when the hall was booked. If not, we should be grateful if you, or whoever booked the hall, would kindly make the necessary arrangements for us. As far as we can judge, we shall not require the help of a typist from Transport House, but we hope that if any unforeseen situation arises we shall be able to call on one for a few hours. Yours sincerely, F. Adler 292/946/21/48